THE INTEGRATION OF ISO 9001, ISO 31000 AND FMEA IMPLEMENTATION TO MAXIMIZE THE COST EFFICIENCY IN PT. SUPERSPRING - Iswanty, Arcindy
PT. Super Spring (Superspring) as one of the startup companies in Indonesia, of course, faces many possible risks. With the early stages of process innovation and reliable product innovation, Superspring must be able to maximize the resources they have to turn the wheels of the company so that it can eventually become an established company. On the other hand, with limited funding, Superspring must be able to reduce costs very efficiently with environmental challenges that are agile and minimal bureaucracy. Risk and opportunity always come like two sides of a coin. The greater the risk, the higher the possibility of return obtained, or even the possibility of failure if it is not anticipated from the start. So the risk must be managed so as to minimize the impact that will be experienced. This research aims to explore the implementation of risk management in start-up company cost efficiency. Start from the business processes identification, risk and opportunity identification, risk analysis, and risk treatment. The risk and opportunity for improvement will be converted into financial conversion or calculated by the financial impact (on value). And finally, the cost comparison of existing costs with the implementation of risk control and implementation of improvement opportunities will be carried out. The research method that will be used is a qualitative approach in which in-depth interviews will be held with the Superspring’s manager level as the primary data to break down the risk in each process including the mitigation action and financial conversion. In addition, it will also be combined with the quantitative approach in calculating the risk and cost-efficiency from internal report data that will be the source for discussion in the in-depth interview process, which is historical loss on risk and analysis of incident or error reports. Using the process approach ISO 9001, risk approach ISO 31000, and FMEA (Failure Mode Effect Analysis), the company is ideal to implement risk management to make it cost-efficient. Based on the calculation done from the core process (the sales process, the IT process, the technical process, the warehouse and logistic process, and the customer service process) analysis, is shown that all over the risk decrease is about 65.54% (from inherent risk to residual risk) and the cost efficiency is about 315%. However, with the addition of action against risk in a lean and anti-rigid environment, it is not immediately applicable. There are some actions that are actually easy and basic to do but are not carried out on the basis of ignorance of best practice, but with the convenience of technology, this should be simplified but with a large enough investment. It is suggested that risk management is best integrated into operational processes in the whole company lifecycle through continuously evaluating risks as the company progresses. This continuous process of evaluating risks as they emerge or change in severity and dealing with them effectively can improve the company's performance outcome. This would mean that each operational process as described in the company lifecycle, would have a rigorous risk and uncertainty assessment.